The quality of the argumentation of the students of the Department of Education regarding heat and temperature - Σαράμπαλη Κασιαλμά, Ρόζα; Στύλος, Γεώργιος; Κώτσης, Κωνσταντίνος (Education Sciences, 2023)
Argumentation is a basic skill of scientific reasoning and is considered an important pursuit of teaching in Science. The purpose of this study is to research the quality of the written arguments of students on the concepts of heat and temperature. The survey sample consisted of 95 first-year students of the Pedagogical Department of Elementary Education of the University of Ioannina. For the collection of data, a questionnaire was used, which included open-ended questions about temperature and heat. The analysis of the students' answers was carried out with scales of graded criteria that assess the level of the structure and content of their arguments. The analysis of the data revealed that the average of the students' arguments about heat and temperature was low. In addition, the outcomes of the research showed that the gender of the students and their educational choice do not correlate with their arguments.